FUNCTIONAL RE-MODELING INFLUENCE OF EPILEPS IN BRAIN TUMOR - A. A. Miranda; V. A. Zhadnov (Эпилепсия и пароксизмальные состояния)
Pathological electrical activity in proximity as well as distant cortical and subcortical zones induced by brain tumors alter the functioning of higher regulatory centers. These bioelectric changes in intricately connected brain functional zones lead to misbalances in compensatory mechanisms in turn influencing unfavorable disease outcome.Objective. This study is aimed at analyzing electroencephalographic (EEG) spectral peculiarities of as well as the peculiarities of cardiac rhythm variability in patients with epilepsy associated brain tumors.Materials and Methods. 72 patients participated in the survey aged from 22 to 83 years, divided into 2 groups: Brain tumor patients with epileptic seizures and brain tumor patients without seizures. The patients included in the study were those admitted to the neurosurgical department at Ryazan state regional hospital. Statistical, geometric and spectral parameters of heart rate variability as well as coherence and cross-correlational EEG analyses used to access the functional states of the patients.Results. The study revealed sympathetic predominance of the autonomic nervous system in patients with epilepsy associated brain tumors as opposed to parasympathetic predominance in non epilepsy associated brain tumors indicating significant stress to regulatory systems and depletion of subcortical reserves of the cardiovascular system, further more stretching the adaptation limits, ultimately leading to depression of autonomic regulatory mechanisms and predominance of central mechanisms of regulation and adaptation.Conclusion. Frequency-amplitude analysis of electroencephalogram and cardiointervalogram allow us to assess the degree of distress of different cortical and subcortical regulatory systems in patients with brain tumors, and is recommended as an additional method of investigation in these patients.